2016
DOI: 10.4238/gmr.15038468
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a and miR-196a2 polymorphisms in ovarian cancer risk

Abstract: ABSTRACT. We investigated the relationship between miR-146a and miR-196a2 genetic polymorphisms and development of ovarian cancer in a Chinese population. A total of 134 patients and 227 control subjects were involved in our study between January 2012 and October 2014 from China-Japan Union Hospital of Jilin University. Genotyping of miR-146a and miR-196a2 was accomplished by polymerase chain reaction coupled with restriction fragment length polymorphism analysis. Unconditional multiple-logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Hao 53 analyzed the data collected from 38 independent studies and concluded that the rs2910164 polymorphism increased the risk of lung cancer and nasopharyngeal cancer, while Wang 41 also reported that rs2910164 polymorphism was a risk factor of lung cancer. Additionally, association of rs2910164 C → G variation to ovarian cancer has been observed 54 . However, there was no relationship of rs2910164 polymorphism and ESCC overall, 29 which is consistent with our study, but we also verified that the rs2910164 C to G mutation could increase the risk of ESCC in both the BMI <24 and ≥ 24 subgroups.…”
Section: Discussionsupporting
confidence: 89%
“…Hao 53 analyzed the data collected from 38 independent studies and concluded that the rs2910164 polymorphism increased the risk of lung cancer and nasopharyngeal cancer, while Wang 41 also reported that rs2910164 polymorphism was a risk factor of lung cancer. Additionally, association of rs2910164 C → G variation to ovarian cancer has been observed 54 . However, there was no relationship of rs2910164 polymorphism and ESCC overall, 29 which is consistent with our study, but we also verified that the rs2910164 C to G mutation could increase the risk of ESCC in both the BMI <24 and ≥ 24 subgroups.…”
Section: Discussionsupporting
confidence: 89%
“…The full texts of the remaining 79 records were evaluated and 10 articles were excluded for the following reasons: insufficient reported data ( n : 4) [16,17,18,19], studying other genes or polymorphisms ( n : 3) [20,21,22], not a case-control design ( n : 2) [23,24], and a duplicate study ( n : 1) [25]. Finally, a total of 69 articles remained [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85<...>…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-eight association studies with a total of 11,071 cases and 12,312 controls were included in the meta-analysis of miR-146a rs2910164 and the risk of female neoplasms (Table 1 and Figure 2) [26,28,32,33,34,35,36,38,42,46,47,50,52,55,60,63,67,68,69,70,73,74,77,78,80,81,83,92]. Among these, there were studies that were carried out among Asians ( n : 20), Caucasians ( n : 5), Africans ( n : 1), or South Americans ( n : 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The targets RNAs of miR-146a include tumor necrosis factor, interleukin-1 receptor-associated kinase 1, interleukin 1beta, tumor necrosis factor receptor-associated factor 6 and the complement factor H genes. Earlier Sun et al (2016) performed experiments with miR-146a expression in ovarian cancer, and they found that in ovarian cancer patient compared to healthy controls GG genotype compared to CC genotype 3.73 times, the CG+GG genotype compared to CC genotype 1.68 times, the GG genotype compared to CG+CC genotype 3.02 times more frequently occur. The difference was significant in all the three comparisons [24].…”
Section: Discussionmentioning
confidence: 99%